2019
DOI: 10.1108/cdi-12-2017-0236
|View full text |Cite
|
Sign up to set email alerts
|

A resource-based perspective on work–family conflict: meta-analytical findings

Abstract: Purpose The purpose of this paper is to provide an updated and theory-driven meta-analysis of work–family conflict (WFC). The authors quantitatively review the relationships between WFC and three pairs of antecedents and several consequences. Design/methodology/approach A meta-analysis was conducted to investigate the research model. Specifically, the authors adopt a resource-based perspective (i.e. conservation of resources (COR) theory) to investigate the relationships between three pairs of antecedents (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 231 publications
4
64
0
1
Order By: Relevance
“…Job demands, broadly defined, may necessitate greater interruptions of non‐work (e.g., being on call), may limit interruptions of work (e.g., bus drivers cannot answer their cell), and may influence perceptions of control over one’s time and focus. Indeed, prior meta‐analytic work has demonstrated that job flexibility and higher autonomy at work relate to having less work–family conflict (Liao, Lau, Hui, & Kong, 2019). Thus, in boundary theory terms, job characteristics can impact boundary flexibility and permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Job demands, broadly defined, may necessitate greater interruptions of non‐work (e.g., being on call), may limit interruptions of work (e.g., bus drivers cannot answer their cell), and may influence perceptions of control over one’s time and focus. Indeed, prior meta‐analytic work has demonstrated that job flexibility and higher autonomy at work relate to having less work–family conflict (Liao, Lau, Hui, & Kong, 2019). Thus, in boundary theory terms, job characteristics can impact boundary flexibility and permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Experiencing adverse, resource-depleting work situations can frustrate employees. It undermines the quality of their personal well-being, their professional functioning, and even their future career prospects (Ilies et al, 2020;Liao et al, 2019). In many cases, this sort of adversity results from the organizational context itself; when they get to work, employees might confront dysfunctional organizational politics (Jam et al, 2017), bullying behaviors by coworkers (Magee et al, 2017), or excessive workloads (Avery et al, 2010), for example.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work on project management or construction management has focused on work-family conflict issues and has examined the consequences of conflict, including burnout [10,11], turnover intention [12], sleep problems [13], organizational commitment [5,14], and project citizenship behavior [5]. A great deal of research on permanent organizations has focused on the detrimental effects of work-family conflict on mental health (e.g., strain [15], subjective well-being [8]), work attitudes (e.g., job satisfaction and life satisfaction [16,17]), and behaviors (e.g., aggressive behavior [18]). The intensive and chronic work-family conflict suffered by construction professionals, such as construction site managers, on-site estimators or operatives, and civil or structural engineers [19,20], is thus likely to undermine their mental health and increase their engagement in problem behaviors.…”
Section: Introductionmentioning
confidence: 99%